Falling behind, again?. IN No free lunch [column] - Habito, Cielito F. (2017)
Myanmar has its own persistent internal problems but it feels like that they are able to move forward fast. While, mentors to Myanmar appear to be stuck in place, held back by deep divisions and endless political bickering, condemned to watch our neighbors pass us by one by one.
Keywords: Myanmar; Economic development